Phylogenomic investigation of an outbreak of fluoroquinolone-resistant Salmonella enterica subsp. enterica serovar Paratyphi A in Phnom Penh, Cambodia. Issue 3 (24th March 2023) - Dusadeepong, Rutaiwan; Delvallez, Gauthier; Cheng, Sokleaph; Meng, Soda; Sreng, Navin; Letchford, Joanne; Choun, Kimcheng; Teav, Syna; Hardy, Liselotte; Jacobs, Jan; Hoang, Tuyet; Seemann, Torsten; et al.
Abstract : In early 2020, the Medical Biology Laboratory of the Pasteur Institute of Cambodia isolated an unusually high number of fluoroquinolone-resistant Salmonella enterica subspecies enterica serovar Paratyphi A strains during its routine bacteriological surveillance activities in Phnom Penh, Cambodia. A public-health investigation was supported by genome sequencing of these Paratyphi A strains to gain insights into the genetic diversity and population structure of a potential outbreak of fluoroquinolone-resistant paratyphoid fever. Comparative genomic and phylodynamic analyses revealed the 2020 strains were descended from a previously described 2013–2015 outbreak of Paratyphi A infections. Our analysis showed sub-lineage 2.3.1 had remained largely susceptible to fluoroquinolone drugs until 2015, but acquired chromosomal resistance to these drugs during six separate events between late 2012 and 2015. The emergence of fluoroquinolone resistance was rapidly followed by the replacement of the original susceptible Paratyphi A population, which led to a dramatic increase of fluoroquinolone-resistant blood-culture-confirmed cases in subsequent years (2016–2020). The rapid acquisition of resistance-conferring mutations in the Paratyphi A population over a 3 year period is suggestive of a strong selective pressure on that population, likely linked with fluoroquinolone use. In turn, emergence of fluoroquinolone resistance has led to increased use of extended-spectrum cephalosporins like ceftriaxone that are becoming the drug of choice for empirical treatment of paratyphoid fever in Cambodia.